The Penerapan Konsep Kendel, Kandel, Bandel, dan Ngandel, untuk Meningkatkan Self Efficacy Siswa SMK Taman Karya Madya Pertambangan Kebumen - Mulyanto, Mulyanto; Mundilarno, Mundilarno; Muhadisin, Muhadisin; Pranoto, Pranoto (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research was to analyze (1) the reality of the patterns of application of the concepts of kendel, kandel, bandel, and ngandel, to increase the self-efficacy of students at SMK Taman Karya Madya Pertambangan Kebumen, (2) supporting and inhibiting factors, and the effectiveness of implementing these concepts. The method used in this research was a qualitative approach. Data analysis steps included data collection through interviews, documentation and observation, data reduction, data display and drawing conclusions. The results of the research showed that (1) the attitudes of kandel, ngandel, kendel and stubborn could increase the readiness of school principals, teachers and students in facing problems and tasks that had to be completed. In other words, the attitude of kandel, ngandel, kendel and stubborn could increase the self-efficacy of school principals, teachers and students of SMK Taman Karya Madya Pertambangan Kebumen; (2) The supporting factor for implementing the concepts of kandel, kendel bamdel, and ngandel was the solidarity and awareness of all educators and education staff to implement Tamansiswa's teachings; (3) There were no inhibiting factors; (4) The application of the concept was very effective.